CRITERIA OF FORMATION OF SOCIAL-PEDAGOGICAL COMPETENCE OF FUTURE PRIMARY SCHOOL TEACHERS IN INCLUSIVE SECONDARY SCHOOL - Zoia Shevtsiv (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2017)
The article aims to justify the formation of criteria and indicators of social-pedagogical competence of the future teachers of primary school of inclusive comprehensive school and to determine its level of development. The objectives are to determine the status of the development problems of professional competence of teachers in inclusive education; essence and structural components of social-pedagogical competence of future primary school teacher of inclusive comprehensive school; criteria, indicators and levels of social-pedagogical competence of future primary school teacher of inclusive comprehensive schools. The education system in Ukraine is gradually transition to inclusive education. Inclusive comprehensive school is being created. It requires a highly qualified primary school teacher who co-teaches regulatory children and children with disability. The article is grounded the necessity of social-pedagogical competence of future teachers of primary school of inclusive comprehensive schools. The essence of social-pedagogical competence of future primary school teacher of inclusive comprehensive schools is defined. The structural components of social-pedagogical competence are characterized. Scientific papers on the issue of formation of competence of experts in various fields are analyzed. The pronunciation for selection and justification criteria and parameters of formation of professional competence is overviewed. The group of the criteria suggested by various scientists from the evaluation of the formation of professional competence of specialists in different fields is considered. The criteria and parameters of evaluating the levels of social-pedagogical competence of future teachers of primary school in inclusive comprehensive schools are selected on the base of the analysis of modern achievements of scientists. Future prospects of research is in developing of a method of diagnosing the levels of social-pedagogical competence of future primary school teacher in inclusive comprehensive school.